Management of information protection based on the integrated implementation of decision support systems - Lakhno, Valeriy; Kozlovskii, Valeriy; Boiko, Yuliia; Mishchenko, Andrii; Opirskyy, Ivan (Eastern-European Journal of Enterprise Technologies, 2017)
We developed the method and the model for managing protection of objects of informatization, based on the integrated implementation of decision support systems for the tasks on cybersecurity. The proposed solutions differ from the existing ones by the possibility to automate the procedure of generating variants for controlling actions using the decision support system, designed as a web application. The described model for the coordination of experts’ opinions is based on the Delphi method. The approach proposed makes it possible to coordinate expert opinions, including to take into account different interval estimates of the degree of protection and information security metrics of the objects of informatization. Results are presented of testing under actual conditions at the enterprises of Ukraine the software complex "Decision support system for managing cyber security of an enterprise ‒ DMSSCSE". The DSS is adapted for the on-line work of experts. It was established that the DSS "DMSSCSE" makes it possible to improve effectiveness of the applied organizational and technical measures to protect objects of informatization. The proposed solutions enabled bringing down the cost of organizing comprehensive information protection systems by 12−15 % compared to the existing methods